KEARIFAN LOKAL SEBAGAI BENTUK KONSERVASI TRADISIONAL SUMBERDAYA ALAM DI DESA TAMILOUW KABUPATEN MALUKU TENGAH - Asraf Wenno; Maya. M.S. Puttileihalat; Yosevita. Th. Latupapua (Program Studi Manajemen Hutan, Pascasarjana Universitas Pattimura, 2021)
The form of local community wisdom is the basic capital in an effort to conserve forest resources. This research was conducted with the aim of knowing the form and benefits of local wisdom of the Sepa Village community in supporting the conservation of forest resources. The data used in this study are primary data and secondary data. Primary data obtained from questionnaires and in-depth interviews, questionnaires addressed to respondents through interview questions guide. Secondary data were obtained from documents related to the research objectives. Data analysis was carried out in a qualitative descriptive manner. A qualitative approach is used to provide reinforcement from the data obtained through interviews and observations and presented in the form of narrative text. The results of the study explain that the forms of local wisdom of the people of Sepa Country are dusung, sasi, pamali places, and sacred places. The benefit of applying wisdom in supporting forest conservation is that at first glance the terminology is full of mystical beliefs, and seems irrational. However, if you absorb it deeply, how the people of Sepa Country have given lessons about the importance of protecting flora and fauna in the environment in order to maintain balance and preserve nature